การบริหารวิชาการของวิทยาลัยอาชีวศึกษาตามแนวคิดการพัฒนาคุณลักษณะผู้ประกอบการของนักศึกษา - บำรุงกิจ นิจิรา; อุสาโห ชญาพิมพ์; ศิริบรรณพิทักษ์ พฤทธิ์ (Journal of Education Studies, Chulalongkorn University, 2019)
The purposes of this research were 1) to study the conceptual framework of entrepreneurial characteristics development of vocational college students and the entrepreneurial characteristics of students, and 2) to study the current and desired levels of academic management practices of vocational education colleges according to the concept of entrepreneurial characteristics development of students. This study was conducted using the descriptive research approach. The samples came from 141 different colleges. Data were gathered from 423 respondents (3 respondents in each institution), which included an administrator, a teacher and a student of each college. The research instruments were the evaluation form and the questionnaires. The data were analyzed using average and standard deviation. The ﬁndings of the study were 1) the conceptual framework of entrepreneurial characteristics development was composed of three continuous stages of learning and practice principles with six different teaching methods within each stage and four entrepreneurial characteristics of students, and 2) the current and desirable stages of academic management of vocational education colleges according to the concept of entrepreneurial characteristics development of students were overall rated at a high level. Moreover, the average of the desirable stage was higher than the average of the current stage in every area of academic management.